Anti-ulcerogenic and anti-ulcerative colitis (UC) activities of seven amines derivatives - Awaad, Amani Shafeek; Alafeefy, Ahmed Mahmoud; Alasmary, Fatmah A.S.; El-Meligy, Reham M.; Alqasoumi, Saleh Ibrahim (King Saud University, 2017)
The Novel target compounds (CP-1-7) were synthesized and tested at doses up to 1000mg/kg for their entitled activities. They exerted promising results without any behavioral changes and mortality in mice. Therefore, according to the results obtained in our study, it could be categorized as highly safe agents for treating UC since substances possessing LD50 higher than 50mg/kg are considered nontoxic. They also possessed a potent anti-ulcerogenic activity with different potentials. The most effective compound was CP-4, it produced 97.7% ulcer protection of control followed by CP-3, which produced 90.3% protection, while the standard drug ranitidine (100mg/kg) produced 49.2% protection. Compound CP-1 showed lowest activity among the current series, it produced 55.5% protection. The target compounds were significantly more effective than the standard in reducing ulcer index. The anti-ulcerative colitis activity was tested using acetic acid induced colitis model. The curative effect of the tested compounds at a dose of 50mg/kg oral administration on rats showed a potent anti-ulcerative colitis activity with different potentials. They induced a significant decrease in ulcer score, ulcer area, ulcer index and weight/length of the colon specimens.The percent protection of control colitis ranged from 66.8% for CP-7 to 22.3% for CP-5; however the percent protection for dexamesathone (0.1. mg/kg) was 59.3%. The effect of the tested compounds CP-7 and CP-3 at dose 50. mg/kg were significantly more effective than dexamesathone (0.1. mg/kg) in reducing all parameters.Liver functions were not affected as there is no effect on the activity of both AST and ALT in animals that received the compounds, so the compounds didn't reveal hepatotoxic manifestation. Although, the results on kidney functions showed that, CP-1 slightly elevated blood urea concentration and CP-3 & CP-4 slightly elevated serum creatinine; no apparent nephrotoxic manifestations were recorded.